Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1053/jlts.2003.50122
|View full text |Cite
|
Sign up to set email alerts
|

Model for End-Stage Liver Disease score does not predict patient or graft survival in living donor liver transplant recipients

Abstract: A dult-to-adult right hepatic lobe living donor liver transplantation (LDLT) has grown rapidly in the setting of a cadaveric organ shortage. 1 Initial outcomes have been promising for both recipients and donors. 2,3 Nevertheless, this treatment must be approached with careful forethought. Criteria for both recipient and donor selection are just evolving. United Network of Organ Sharing (UNOS) status 2A proved to be an important recipient exclusionary criterion because such patients have threefold greater morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 12 publications
2
64
1
1
Order By: Relevance
“…The performance of the MELD score in predicting posttransplant survival has been more variable (9)(10)(11)(12)(13) but it is generally accepted that patients with very high MELD scores prior to transplant have worse outcomes than those with lower MELDs. With discussion of incorporation of the delta-MELD into organ allocation systems, the question of whether patients with high pretransplant delta-MELD scores have worse posttransplant outcomes would be critical in determining if this change in allocation system would increase posttransplant death rates.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the MELD score in predicting posttransplant survival has been more variable (9)(10)(11)(12)(13) but it is generally accepted that patients with very high MELD scores prior to transplant have worse outcomes than those with lower MELDs. With discussion of incorporation of the delta-MELD into organ allocation systems, the question of whether patients with high pretransplant delta-MELD scores have worse posttransplant outcomes would be critical in determining if this change in allocation system would increase posttransplant death rates.…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies correlating pretransplant MELD score with survival after living donor liver transplantation (6,20,33,35) . Hayashi et al (20) found no association between MELD score and patient survival in living donor liver transplantation recipients. However, the MELD scores were low in that study even among patients who died.…”
Section: Discussionmentioning
confidence: 99%
“…There have been sporadic case reports from Asian regions [31][32][33][34] , as well as from the West [35][36][37][38][39] , of LDLT for PSC from living related donors since then, but none reported recurrence; follow-up periods were less than 2 years in most case reports. Aside from the above case reports, cases of LDLT for PSC are found in moderate to large registries worldwide [40][41][42][43][44] . Moon et al [40] reported 2 cases of LDLT for PSC among their large series of 580 LDLTs.…”
Section: Pscmentioning
confidence: 94%